Increasing Patient Activation at a Student-Run Free Clinic: Effectiveness of a Health Education Intervention - Ritika Dutta; Emmy Shearer; Luis Garcia; Helen Liu; Joshua Swee; Seul Ku; Cara Lai; Steven Lin; Tamara Montacute; Mina Charon (Journal of Student-Run Clinics, 2021)
Background: Free clinics can serve as an important source of health information among underserved populations; however, it is difficult to track the effectiveness of health education interventions for these patients.  Thus, the objective of our study was to develop and assess the impact of a health education intervention in a student-run free clinic setting.Methods: A quality improvement project was implemented in which surveys were used to assess four confidence and knowledge measures among patients who did or did not receive health education from undergraduate volunteers. Statistical significance was determined using studentâ€™s t-tests.Results: Patients who received health education from undergraduate volunteers during clinic visits reported increased confidence in their ability to manage health conditions (p<0.01), knowledge of their prescribed medications (p<0.05), and ability to manage their symptoms (p<0.05) after clinic visits compared to before their clinic visits.Discussion: Dedicated health education interventions by undergraduate volunteers during free clinic visits can lead to increased patient confidence and knowledge of their health conditions. Due to their iterative nature and ease of implementation, quality improvement frameworks may be a useful way to track the efficacy of health education programs in the free clinic setting.